PERKEMBANGAN ILMU-ILMU AL-QUR’AN: STUDI KRITIS TERHADAP KONSEP DAN SEJARAH ULUMUL QUR’AN - Hidayat, Asrul; Rahman, Pathur (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2025)
The Qur’anic sciences (Ulumul Qur’an) represent a fundamental branch of Islamic scholarship that serves as the foundation for understanding the meaning and message of the Qur’an comprehensively. This study aims to critically analyze the basic concepts, scope, and historical development of Ulumul Qur’an from the classical to the contemporary period. Using a qualitative approach and library research method, this paper examines primary and secondary sources such as the works of al-Zarkasyi, al-Suyuthi, and modern scholars who discuss the epistemology of Qur’anic studies. The findings reveal that Ulumul Qur’an has undergone a significant evolution both terminologically and methodologically. In the early Islamic period, it developed through oral and traditional transmission by the companions and successors. During the codification era, numerous systematic works emerged, laying the foundations of Qur’anic sciences as an independent discipline. In the modern era, Ulumul Qur’an continues to expand through interdisciplinary approaches involving linguistics, history, and hermeneutics, aiming to address contemporary issues faced by Muslim societies. This study concludes that understanding the development of Qur’anic sciences is essential for strengthening the epistemological framework of Islamic scholarship and for developing interpretative methodologies relevant to modern contexts. Hence, this research contributes to enriching the academic discourse on Islamic studies through a critical exploration of the conceptual and historical dynamics of Ulumul Qur’an.